PENGARUH PRODUK, HARGA, BRAND IMAGE, DAN PROMOSI TERHADAP PEMBELIAN ULANG PADA AYAM GEPREK MAK JOSS - Longginus Lamauring; Rena Febrita Sarie (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to examine and analyze the effect of product, price, brand, and promotion on geprek mak joss chicken Jalan Sememi Jaya No.4 West Surabaya. The sampling technique used in this study is the side accidental technique. The population of this study were buyers who happened to be met from May to July 2022, with a total of 75 respondents. Analysis of the data in this study using multiple linear regression test with Statistical Product and Service Solutions (SPSS). The results of this study indicate that the research variables Product (X1), Price (X2), Brand Image (X3) and Promotion (X4) have a significant effect on Repurchase (Y) in this study providing an effect of 79.2%. while the remaining 20.8% is other outside influences that are not included in the calculation model.